Three dimensional craniofacial anthropometry using stereophotogrammetry: validation of the technique - Majid, Zulkepli; Chong, Albert K.; Setan, Halim; Ahmad, Anuar (2005)

(untitled)
Craniofacial anthropometric mark mapping was performed using stereo-photogrammetry technique. Various size and shape of control frames were designed to provide three-dimensional object-space control for stereo images. A research was carried out to determine whether the accuracy could be further enhanced using natural points. In the research, control points and natural points were measured using precision software and their coordinates computed via bundle adjustment technique. In addition, the sixcamera stereo-photogrammetric system was electronically synchronized for optimum accuracy. Subsequently, Digital Video Plotter (DVP) digital photogrammetric workstation was used for stereo orientation and stereo-digitizing of the anthropometric landmarks. For the accuracy assessment of the ‘natural point’ technique, absolute orientation was performed on the stereo-model using control-frame control and natural points respectively. The results show that the developed technique improves the accuracy of 0.6mm with one standard deviation. The optimum accuracy of the setup stereophotogrammetric cameras was 0.25mm.